Effects of Prior Knowledge on Decisions Made Under Perceptual vs. Categorical Uncertainty - Hansen, Kathleen; Hillenbrand, Sarah; Ungerleider, Leslie (Frontiers in Neuroscience, 2012)
Humans use prior knowledge to bias decisions made under uncertainty. In this fMRI study we predicted that different brain dynamics play a role when prior knowledge is added to decisions made under perceptual vs. categorical uncertainty. Subjects decided whether shapes belonged to Category S – smoother – or Category B – bumpier – under both uncertainty conditions, with or without prior knowledge cues. When present, the prior knowledge cue, 80/20 or 50/50, indicated that 80% and 20% (or 50% and 50%) were the chances that responding "S" and "B" (or vice versa) would be correct. During perceptual uncertainty, shapes were degraded with noise. During categorical uncertainty, shapes were ambiguous. Adding the 80/20 cue increased activation during perceptual uncertainty in bilateral lateral occipital cortex and left middle frontal gyrus (MidFG), and decreased activity in bilateral lateral occipital cortex during categorical uncertainty. Right MidFG and other frontoparietal regions were active in all conditions. The results demonstrate that left MidFG shows activation changes, suggestive of an influence on visual cortex, that depend on the factor that makes the decisions difficult. When sensory evidence is difficult to perceive, prior knowledge increases visual cortical activity. When the sensory evidence is easy to perceive but difficult to interpret, prior knowledge decreases visual cortical activity.